(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
A study on healthy male and female volunteers was conducted. The study included 800 people: 300 men with a mean age of 40.5 ± 2.4 and 500 women with a mean age of 43 ± 3.2. Those examined were divided into 2 groups homogenous for gender. Objective: 1. To study the effectiveness of thermoalgometry with a complex estimation of psychophysiological parameters to determine the pain status in volunteers. 2. To find parameters of pain resistance and peculiarities of pain status depending on gender, age, and psychophysiological parameters of the subjects. Methods. The level of pain sensitivity was determined using thermoalgometry and tensoalgometry. The mean arterial pressure (MAP) was determined non-invasively to find out how the pain threshold affects the hemodynamics in volunteers. The psychophysiological state was evaluated with Spielberg’s State-Trait Inventory (STAI). Results. Groups 1 and 2 involve the following groups of subjects: 1. A group with estimated resistance to pain stimuli. Thermoalgometry: 90 to 200 ms; VAS scoring in tensoalgometry: 0-2; low or moderate levels of anxiety according to Spielberg’s Inventory scoring. 2. A group with estimated moderate resistance to pain stimuli. Thermoalgometry: 60 to 89 ms; VAS scoring in tensoalgometry: 1-3; moderate levels of anxiety according to Spielberg’s Inventory scoring. 3. A group with estimated susceptibility to pain stimuli. Thermoalgometry: 10 to 40 ms; VAS scoring in tensoalgometry: 3-4; moderate or high levels of anxiety according to Spielberg’s Inventory scoring. A direct correlation between age and reaction time to a stimulus in thermoalgometry was found (р<0.001). Mean values of thermoalgometry were gender-dependent. Significant correlation with moderately resistant and low (susceptible) pain sensitivity was determined in subjects with high values of trait and state anxiety. Conclusions. The effectiveness of thermoalgometry combined with a complex estimation of psychophysiological parameters was established to determine the pain status in volunteers. Pain resistance values and pain status peculiarities were set depending on gender, age, and psychophysiological parameters of the subjects. The obtained data can be used in clinical practice to implement the pain management personified approach to improve life quality.